2015
DOI: 10.1002/ijc.29910
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosoma cruzi extracts elicit protective immune response against chemically induced colon and mammary cancers

Abstract: Trypanosoma cruzi, the protozoan parasite that causes Chagas' disease, has anticancer effects mediated, at least in part, by parasitederived products which inhibit growth of tumor cells. We investigated whether immunity to T. cruzi antigens could induce antitumor activity, using two rat models which reproduce human carcinogenesis: colon cancer induced by 1,2-dimethylhydrazine (DMH), and mammary cancer induced by N-nitroso-N-methylurea (NMU). We found that vaccination with T. cruzi epimastigote lysates strongly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
43
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 49 publications
1
43
0
3
Order By: Relevance
“…Immunization with T. cruzi epimastigote lysate strongly inhibited tumor development in vivo by inducing the activation of both CD4(+) and CD8(+) T cells as well as by increasing numbers of CD11b/c(+) His48(−) MHC II(+) cells, which correspond to macrophages and/or dendritic cells. Antibodies against T. cruzi lysate recognized various rat and human tumor cell types such as colon and human breast cancer cells and thus mediate tumor cell killing through antibody-dependent cellular cytotoxicity (ADCC) (Ubillos et al, 2016). To illustrate this mechanism, studies have identified a parasite chaperone molecule, the T. cruzi calreticulin (TcCRT) (Aguillon et al, 2000) and demonstrated its potent antiangiogenic and antitumor effects both in-vitro and in-vivo .…”
Section: Paradoxical Dual Impacts Of Chagas Disease In Carcinogenesismentioning
confidence: 99%
“…Immunization with T. cruzi epimastigote lysate strongly inhibited tumor development in vivo by inducing the activation of both CD4(+) and CD8(+) T cells as well as by increasing numbers of CD11b/c(+) His48(−) MHC II(+) cells, which correspond to macrophages and/or dendritic cells. Antibodies against T. cruzi lysate recognized various rat and human tumor cell types such as colon and human breast cancer cells and thus mediate tumor cell killing through antibody-dependent cellular cytotoxicity (ADCC) (Ubillos et al, 2016). To illustrate this mechanism, studies have identified a parasite chaperone molecule, the T. cruzi calreticulin (TcCRT) (Aguillon et al, 2000) and demonstrated its potent antiangiogenic and antitumor effects both in-vitro and in-vivo .…”
Section: Paradoxical Dual Impacts Of Chagas Disease In Carcinogenesismentioning
confidence: 99%
“…In a word, the antioxidant, anti-inflammatory, and immunomodulatory effects of spices have been confirmed in many studies [6]. Therefore, spices could be used to prevent and treat cancers, because oxidative stress [7,8,9,10,11,12], inflammatory stress [13,14] and immune response [15,16] have been associated with the genesis, growth, and metastasis of cancers [17,18,19]. In fact, epidemiological and experimental evidences have shown that certain spices might lower risks of some cancers [20,21,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…We have read with great interest the study by Ubillos et al 1 Using in vitro and in vivo experimental approaches the authors reported very interesting results, showing that a vaccine built from Trypanosoma cruzi antigens protects against the development of chemically induced colon and mammary cancers in mice. From a theoretical point of view, to conceive their vaccine strategy the authors have appropriated a recent rational basis that attributes potential molecular homology between antigens of parasite and cancerous cells.…”
Section: Dear Editormentioning
confidence: 99%